Origen : cosmology and ontology of time - Tzamalikos, P. 1951- (Vigiliae Christianae, Supplements, 2006)
Origen's Cosmology and Ontology of Time constitute a major catalyst and a massive transformation in the development of Christian doctrine. The author challenges the widespread impression about this theology being bowled head over heels by its encounter with Platonism, Gnosticism, or Neoplatonism, and casts new light on Origen's grasp of the relation between Hellenism, Hebrew thought and Christianity. Against all ancient and modern accounts, the ingrained claim that Origen sustained the theory of a beginningless world is disconfirmed. He is argued to be the anticipator and forerunner of critical notions, with his innovations never having been superseded. While some of the accounts afforded by subsequent Christian writers were more extended, they were not fuller. Of them, Augustine just fell short of even accurately echoing this Theory of Time, since he introduced affinity with Platonism at points where Origen had instituted a radical dissimilarity. With his background fruitfully brought into the study of these questions, Origen's propositions are genuine innovations, not mere advances, however massive.